IMPLEMENTASI BIMBINGAN KONSELING DALAM MERUBAH PERILAKU SISWA SD NEGERI 04 PARDASUKA - Trylaksono, Dimas Bayu (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study aims to describe: (1) implementation of counseling guidance in SD Negeri 04 Pardasuka in changing student behavior, (2) role of teacher and principal on implementation counseling guidance in changing student behavior in SD Negeri 04 Pardasuka. This research is a qualitative research. The subjects of this study were principals, teachers, and students. Data collection techniques used are observation techniques, interviews, documentation. Analytical techniques used consisted of three components of analysis, namely data reduction, data presentation, and withdrawal of conclusions or verification. This research begins with the preparation stage, the implementation of research, the preparation of reports and ending with reporting. The result of this research is the implementation of counseling guidance in SD Negeri 04 Pardasuka done through stage of planning, implementation, evaluation, and follow up. Students who have poor behavior are advised, guided and directed by individual approaches done by principals and teachers, so that later can be formed good behavior, develop its potential and directed talent and interest of students. Implementation of this counseling guidance can also solve problems faced by students at school and at home.Keyword: guidedance and counseling, behavior, role of teacher and principal.